A Comparative Study on Inclination Towards Entrepreneurship Among Male and Female Management Students in Semi Urban Towns With Special Reference to Kanchipuram - Vinuchakravarthi, V.; Srinivasan, S. (AMC Indian Journal of Entrepreneurship, 2020)
The government of India has taken lot of initiatives like Start up India, Institutional Innovation Council, and encouraging incubators with the priority of creating entrepreneurs across all communities. Whether these are first generation entrepreneurs or next generation entrepreneurs from traditional family businesses, today there are lot of platforms available to promote entrepreneurship starting from the institutional level and then there are other sources to develop them further. This paper was an attempt to identify the inclination of management graduates towards entrepreneurship and further we also attempted to do a comparative study of ambition and its influencing factors in semi urban town. This paper analysed students’ opinion about entrepreneurship, the challenging factors, the inspiration and role played by the institution, internet etc. The study has revealed a better picture where students have a zeal for entrepreneurship and have better understanding about it.